Partial neuroprotection by 17-β-estradiol in neonatal gamma-irradiated rat cerebellum - Zorrilla Zubilete, María Aurelia (2011)
Acute and long-term complications can occur in patients receiving radiation therapy. It has been suggested that cytoprotection might decrease the incidence and severity of therapy-related toxicity in these patients. Developing cerebellum is highly radiosensitive and for that reason it is a useful structure to test potential neuroprotective substances to prevent radiation induced abnormalities. Recent studies have shown that estrogen can rapidly modulate intracellular signalling pathways involved in cell survival. Thus, it has been demonstrated that estrogens mediate neuroprotection by promoting growth, cell survival and by preventing axonal pruning. The aim of this work was to evaluate the effect of the treatment with 17-β-estradiol on the motor, structural and biochemical changes induced by neonatal ionizing radiation exposure, and to investigate the participation of nitric oxide and protein kinase C, two important intracellular messengers involved in neuronal activity. Our results show that perinatal chronic 17-β-estradiol treatment partially protects against radiation-induced cerebellar disorganization and motor abnormalities. PKC and NOS activities could be implicated in its neuroprotective mechanisms. These data provide new evidence about the mechanisms underlying estrogen neuroprotection, which could have therapeutic relevance for patients treated with radiotherapy.